THE EFFECT OF SERVICE QUALITY, EASE OF USE AND SECURITY OF PLN MOBILE APPLICATION TRANSACTIONS ON USER SATISFACTION - Nadia Desti Chaerunisa; Andala Rama Putra Barusman (International Journal of Multidisciplinary Reseach, 2026)
The purpose of this study is to determine the effect of service quality, ease of use, and transaction security on user satisfaction of the PLN Mobile application. This study uses a quantititative approach with a survey method, conducted by distributing questionnaires to students of Universitas Bandar Lampung as users of the PLN Mobile application. The sample was determined using the Lemeshow formula and purposive sample technique, resulting in 128 respondents who met the reseacrh criteria. The data were analyzed using statiscal calculatuions with the help of SPSS vesion 26. The results show that service quality, ease of use, and transaction security simutaneously have a significant efeect on user satisfaction. Partially, each independent variable also has a positive and significant effect on user satisfaction. These findings show that improving service quality, ease of use, and transaction security can increase user satisfaction with the PLN Mobile application. This study can provid an indirect contribution to PLN (Persero) and application developers in improving digital-based service quality, ease of use, and transaction security, as well as a reference for future reseach related to this topic.